Antimicrobial Properties of Medicinal Plants in the Lower Area of Ie Seu-um Geothermal Outflow, Indonesia - Fakri, Fajar; Harahap, Saima Putri; Muhni, Akmal; Khairan, Khairan; Hewindati, Yuni Tri; Idroes, Ghazi Mauer (Heca Sentra Analitika, 2023)
The lower area of the Ie Seu-um manifestation, located in Ie Seu-um village, Aceh Besar District, harbors several medicinal plants that exhibit potential for the treatment of infectious diseases. This study aims to assess the secondary metabolite content and in vitro antimicrobial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans of medicinal plants inhabiting the geothermal region. Medicinal plants, namely Pluchea indica (L.) Less., Acrostichum aureum L., Acacia mangium L., and Calotropis gigantea (L.) Dryand., were collected within a range of 100-150 meters from the hot springs in the lower area. Methanol extracts of these medicinal plants underwent phytochemical screening and were tested for antimicrobial activity using the Kirby-Bauer disc diffusion method at a concentration of 50%. The results of phytochemical screening demonstrated positive variations in alkaloids, flavonoids, saponins, steroids, triterpenoids, and tannins for each medicinal plant. The antimicrobial activity of the methanol extracts noticeably inhibited the growth of S. aureus compared to E. coli and C. albicans. The largest inhibition zones were observed for the leaf part of A. mangium (12.70 ± 2.30 mm) against S. aureus, the aerial part of A. aureum (11.57 ± 2.01 mm) against E. coli, and the aerial part of P. indica (9.89 ± 1.11 mm) against C. albicans. Based on the research findings, medicinal plants originating from the lower area of the Ie Seu-um manifestation exhibit potential as antimicrobial agents, particularly against gram-positive bacteria.